2013
DOI: 10.1182/blood.v122.21.3977.3977
|View full text |Cite
|
Sign up to set email alerts
|

The BIM Deletion Polymorphism: A Paradigm Of a Permissive Interaction Between Germline and Acquired TKI Resistance Factors In Chronic Myeloid Leukemia

Abstract: Germline polymorphisms and tumor-specific genetic mutations together contribute to the behavior of human cancers, including the response to therapy. However, few specific models allow for the detailed study of how inherited and acquired genetic factors interact to cause clinical drug resistance, nor how their interaction can be prevented or overcome. We recently reported a germline deletion polymorphism in the BIM gene that was sufficient to mediate intrinsic resistance to targeted therapies in cancer, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…One possible 5 BioMed Research International strategy to overcome the resistance and restore the response to TKIs is adding BH3-mimetic drug or histone deacetylase (HDAC) inhibition. In vitro experiments revealed that the addition of BH3-mimetic drug ABT-737 with imatinib enhanced the TKI-induced apoptosis and cell death in deletion-containing cells [18,47]. The other studies demonstrated that the HDAC inhibitor vorinostat could circumvent TKI resistance in EGFR-mutant NSCLC cell lines harboring BIM deletion polymorphism [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…One possible 5 BioMed Research International strategy to overcome the resistance and restore the response to TKIs is adding BH3-mimetic drug or histone deacetylase (HDAC) inhibition. In vitro experiments revealed that the addition of BH3-mimetic drug ABT-737 with imatinib enhanced the TKI-induced apoptosis and cell death in deletion-containing cells [18,47]. The other studies demonstrated that the HDAC inhibitor vorinostat could circumvent TKI resistance in EGFR-mutant NSCLC cell lines harboring BIM deletion polymorphism [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MDR1 variants, day29 plasma imatinib level of > 1757 ng/mL, lower ABCA6, ABCC4 RNA expression as well as achieving EMR at 3, 6 months and MMR at 12 months were associated with significantly better FFS. While increased ABCC4 RNA expression has been reported previously in suboptimal response to imatinib 15,17,21,22,26 , the role on increased ABCA6 on imatinib response is not clear.…”
Section: Discussionmentioning
confidence: 89%
“…In melanoma, a 61 kDa isoform encoded by a BRAF splice variant missing exons 4-8 lacks the RAS-binding domain, resulting in constitutive isoform dimerization and kinase activity and resistance to the inhibitor vemurafenib (32). A splice variant of BIM (BIM-g), encoding a protein that lacks the BH3 domain, has been identified as a mechanism for TKI (e.g., imatinib and gefitinib) resistance in chronic myeloid leukemia (33)(34)(35). It should be noted that none of these splicing events occur within the tyrosine kinase domain.…”
Section: Discussionmentioning
confidence: 99%